Legal Challenges and Enforcement Strategies: Bawaslu's Role in Addressing Election Violations in Indonesia's 2024 Simultaneous Elections - Nikmah, Faridhatun (El-Aqwal : Journal of Sharia and Comparative Law, 2024)
Elections are a very important momentum for the community. This is because the community has the opportunity to determine the future leaders of the Indonesian nation in the next five years. Therefore, in making the election a success is not only the responsibility of Bawaslu as a supervisory institution, but also the obligation of all Indonesian people. The implementation of the 2024 election has many challenges in making the election a success, so it is necessary to have a role for Bawaslu in enforcing the law. The purpose of this study is to describe the challenges carried out by Bawaslu in enforcing violations of the law in Indonesia. The method of this research is qualitative descriptive. The results of this study show that there are four challenges for Bawaslu in the 2024 elections, including identity politics, money politics, neutralization of ASN, TNI, and Polri in election campaigns, and the spread of hoax news. In this case, it shows that Bawaslu plays an important role in law enforcement of simultaneous election violations in 2024. With the role played by Bawaslu in law enforcement, it can create a democratic and just country for the community.